Chapter 1 Understanding youth transitions in difficult times - Irwin, Sarah (Taylor & Francis, 2018)
This chapter sketches some key developments in the framing of youth and early adulthood as life course stages, and situates the influence of the recent economic recession with reference to longer-term trends including increased social inequality. The authors explore different aspects of youth and early adulthood as these relate to labour market and family transitions and inter-generational relationships. These are illustrated by developments across the European nations represented in the book, specifically Norway, the UK, Germany, Greece, Portugal and Italy. The authors discuss the theoretical foundations of youth studies and life course research and set the context for the collection as well as framing the chapters in the book.